2006
DOI: 10.1111/j.1099-0860.2006.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

What Works in Strategic Partnerships for Children: a Research Review

Abstract: Strategic partnerships have a key role to play in delivering the government's ‘Every Child Matters’ agenda. There is a developing body of research and other evidence and practice‐informed literature about what works in relation to partnership working. Drawing on a research review commissioned by Barnardos on strategic partnership working for children, this study summarises research findings from a number of sectors relating to the development, delivery and review of effective partnerships. Although there is wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 9 publications
1
35
1
1
Order By: Relevance
“…The concept of inter-or multi-agency collaboration is often used to explain such models (for instance, Johansson 2011Johansson , 2012; however, the meaning of multi-agency collaboration is rarely spelled out. Several scholars point to the confusing terminology used to describe collaborative arrangements and multi-agency activity, which makes classification and comparison difficult (Atkinson et al 2007;Percy-Smith 2006;Blacklock and Phillips 2015). Different researchers use words such as partnership, joined-up, coordinated, integrated, co-located, and more for such arrangements.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The concept of inter-or multi-agency collaboration is often used to explain such models (for instance, Johansson 2011Johansson , 2012; however, the meaning of multi-agency collaboration is rarely spelled out. Several scholars point to the confusing terminology used to describe collaborative arrangements and multi-agency activity, which makes classification and comparison difficult (Atkinson et al 2007;Percy-Smith 2006;Blacklock and Phillips 2015). Different researchers use words such as partnership, joined-up, coordinated, integrated, co-located, and more for such arrangements.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This reform agenda for the delivery of children's services entailed both the improvement and integration of universal services, such as in early years' settings and schools, and the reconfiguration of family support services around children and families in one place, and delivered by multi-disciplinary teams, as in Childrens' Centres and Extended Schools (Pugh, 2006). Despite this becoming a major element of Labour's childcare policies, evidence of any direct impact on the uptake of childcare and family support, and resulting implications for child poverty levels, was scant, while the effectiveness of strategic partnerships remained in doubt (Percy-Smith, 2006).…”
Section: Refocusing Childcare Family Support and Child Poverty Stratmentioning
confidence: 99%
“…It has been suggested that when thinking about collaborative or integrated services it is useful to consider a continuum of integration from organisations working totally independently and coming together for specific tasks to complete merging of services (Percy-Smith, 2005;Townsley et al 2004). There is a considerable literature exploring the factors that help or hinder collaborative working, although it needs to be noted that the evidence in relation to outcomes of integrated work on the lives of children and families is limited (Marsh, 2006 andSloper, 2004).…”
Section: Introductionmentioning
confidence: 99%